2021
DOI: 10.1515/jbcpp-2020-0225
|View full text |Cite
|
Sign up to set email alerts
|

Effects of date seeds administration on anxiety and depressive symptoms in streptozotocin-induced diabetic rats: biochemical and behavioral evidences

Abstract: Objectives Several epidemiological data indicate that chronic hyperglycemia is associated with behavioral changes such as anxiety and depressive symptoms. Date seeds, one of the most potent products with potential antioxidant activities and possess many benefits against hyperglycemia and its complication. The aim of the current study was to explore the potential effect of date seeds extract on biochemical and behavioral changes (anxiety and depression) in streptozotocin (STZ)-diabetic rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 66 publications
4
4
0
Order By: Relevance
“…The results from this study revealed that DM led to characteristic anxiety and depressive-like behaviors, as indicated by the increase in immobility duration (FST), decrease in entries and time spent in the open arms (EPMT) as well as reduction in the number of crossing and rearing (OFT), which were in corroboration with previous studies on DM-induced anxiety and depression [ 8 , 26 , 31 , 32 ]. Metabolic disorders, including diabetes and obesity, have been prominently associated a number of psychological problems particularly major depressive disorders and anxiety, and hyperglycemia is a prevalent factor that can modulate the onset, progression and deterioration of depression and anxiety [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…The results from this study revealed that DM led to characteristic anxiety and depressive-like behaviors, as indicated by the increase in immobility duration (FST), decrease in entries and time spent in the open arms (EPMT) as well as reduction in the number of crossing and rearing (OFT), which were in corroboration with previous studies on DM-induced anxiety and depression [ 8 , 26 , 31 , 32 ]. Metabolic disorders, including diabetes and obesity, have been prominently associated a number of psychological problems particularly major depressive disorders and anxiety, and hyperglycemia is a prevalent factor that can modulate the onset, progression and deterioration of depression and anxiety [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…Insulin supplemented with PFC had more significant effects on anxiety than only insulin treatment in STZ-diabetic rats exposed to CMS, as revealed by the decreased symptoms assessed using the OFT and EPM tests. This anxiolytic-like effect of insulin has previously been reported in STZ-diabetic rats (53). The current study is the first report that shows this treatment combination has these effects on STZ rat model of diabetes under stress conditions.…”
Section: Discussionsupporting
confidence: 84%
“…One reason for these findings could be explained by the experimental procedures and the total duration of stress exposition. In this line, antidepressant-like effects of insulin were previously reported in STZ-diabetics rats (21,53,64). Contrariwise, our results revealed that stressed diabetic rats treated with insulin were less likely to decrease the immobility time in FST, indicating the absence of any significant antidepressant effect of insulin in this model of rats.…”
Section: Discussionsupporting
confidence: 80%
“…In daily life, the anxiety-associated behaviors can be induced by many factors, such as repeated social defeat stress [ 6 , 30 ], high-fat intake [ 31 ], and metabolic disturbance [ 32 ]. Rocha-Gomes et al reported that a low dose of LPS injection during mouse gestation can induce a preventive effect on anxiety-like behaviors and neuroinflammatory responses in the amygdala in high-fat-fed dam’s adolescent offspring [ 33 ].…”
Section: Discussionmentioning
confidence: 99%